Genotype and Environmental Factors Affecting Birth and Postnatal Weights of Prolific Javanese Sheep - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: A study to evaluate the effect of genotype of dam (Feell+Fcc1+, Fee.l+Feck: EixilTecJI"